National plumbing codes handbook - Woodson, R. Dodge (McGraw-Hill, 1993)
The "National Plumbing Codes Handbook" contains in-depth coverage of: proper methods of installing drainage systems; requirements for proper use of all types of vents; code regulations for potable water systems - from street connections to fixture connections; correct methods for all types of plumbing fixture installations; specialty devices such as traps, clean-outs, interceptors, and back-water valves; all commonly encountered plumbing materials and their uses; and gas piping basics. The "Handbook" also provides guidance on how code enforcement works, how the plumbing codes are administered, and how plumbers should prepare their work for inspection. Filled with charts, tables, and more than 200 illustrations, this book should be a useful source for all plumbing professionals.